Analyzing the electric vehicle acceptance, transition scenarios and its impact on electricity demandand GHG emissions in Pakistan - Butt, Muhammad Huzaifa; Singh, Jai Govind; Roy, Joyashree; Weerakorn Ongsakul; Asian Development Bank-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
This work aims to investigate the factors accelerating electric vehicle (EV) acceptance at the consumer end in Pakistan, its impact on annual energy demand and its role in reducing CO2 emissions from the transport sector. The first part of the study uses the quantitative analysis method with the survey as an instrument for data collection. The model under investigation was adapted from the famous Technology Acceptance Models (TAMs) and modified with other significant predictors evidenced in the literature. Correlation and stepwise regressing were performed with a multicollinearity check for model hypothesis testing. Out of six predictors, only four factors were significant in accelerating the EV transition and the proposed model explains 56.3% of the variance in intention to buy EV. Financial policies were highly significant as one standard deviation unit increase in financial policy can increase public intention to buy EV by 0.476 standard deviation units. The second significant factor affecting the choice to buy is an environmental concern, followed by the facilitating conditions and perceived ease of use. The second part of the study used three exponential smoothing models for forecasting two, three and four-wheeler demand and building scenarios for EV penetration. Later, a mathematical model calculates annual energy demand and CO2 emissions based on the type of vehicle and fuel consumed. The results highlight that the Pakistan transport demand will reach 54 million by 2040 from 27 million units in 2020. Throughout the timeline, the two-wheeler share is more dominant than 80%. In the current policy scenario, deep decarbonization of the transport sector is not possible; only 40% of EV two-wheeler and 25% of EV four-wheelers will be there by 2040; the rest will be traditional vehicles. In the current policy scenario (NEVP), electricity energy demand will be 20,450 GWh and fossil fuel demand will be limited to 12.2 MT compared to 19 MT without EV case by 2040. The CO2 emissions will be limited to 48 MT in NEVP instead of 61.6 MT without an EV case. However, due to electricity's high emissions factor, the EV transition will result in 8.3 MT of CO2 emissions in 2040. Therefore, a clean energy mix is essential for maximizing the benefits of EV transition.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering Sustainable Energy Transition
Thesis (M. Eng.) - Asian Institute of Technology, 2022
Keywords: Electric vehicles -- Environmental aspects -- Pakistan; Greenhouse gas mitigation -- Environmental aspects -- Pakistan